Case report: sebaceous adenitis in an Akita dog, clinical management and remission with emphasis on topical therapy (Research, Society and Development, 2025)
The objective of this article is to present a case report of sebaceous adenitis in an Akita dog, including its clinical management and remission, with emphasis on topical therapy. A qualitative, descriptive clinical case study was conducted. Sebaceous adenitis is a rare dermatopathy characterized by inflammatory atrophy of sebaceous glands and coat alterations. It can affect dogs of any age or sex, with predisposition in breeds such as Standard Poodles and Akitas. Clinical signs vary according to hair type and include alopecia, scaling, hyperkeratosis, and follicular casts. Definitive diagnosis is performed through histopathological examination, and is essential to exclude other differential diagnosis, such as demodicosis, dermatophytosis, seborrheic disorders, and endocrinopathies. Treatment aims to reduce clinical signs, control scaling, and improve coat quality.